Bektashi’s In The Light Of Ottoman Deed And Tahrir Books (Xv.-Xvi Centuries) - Steinherr, Irène Beldiceanu (Journal of Alevism-Bektashism Studies, 2010)
This article gives information on Bektashi and the Bektashism based on the Tahrir books dated end 15th and start of 16th centuries. After close investigation of these books belonging to the reign of Mehmet the 2nd and Beyazit the 2nd, it gives information on the Aksaray sanjak only. In the Tahrir books information is presented only on the Dergah and Zaviyes limited with the Bektashi and the name of Haci Bekta Veli. Info will be not only the status but also with the belief structures.”
Keywords: keyword